Three Candida albicans potassium uptake systems differ in their ability to provide Saccharomyces cerevisiae trk1trk2 mutants with necessary potassium - Elicharová, Hana; Hušeková, Barbora; Sychrová, Hana (FEMS yeast research, 2016)
Yeasts usually have one or two high-affinity potassium transporters. Two complete and one interrupted gene encoding three types of putative potassium uptake system exist in Candida albicans SC5314. As high intracellular potassium is essential for many yeast cell functions, the existence of three transporters with differing transport mechanisms (Trk uniporter, Hak cation-proton symporter, Acu ATPase) may help pathogenic C. albicans cells to acquire the necessary potassium in various organs and tissues of the host. When expressed in Saccharomyces cerevisiae lacking their own potassium uptake systems, all three putative transporters were able to provide cells with the ability to grow with low amounts of potassium over a broad range of external pH. Only CaTrk1 was properly recognized and secreted to the plasma membrane. Nevertheless, even the small number of CaHak1 and mainly CaAcu1 molecules which reached the plasma membrane resulted in an improved growth of cells in low potassium concentrations, suggesting a high affinity and capacity of the transporters. A single-point mutation restored the complete CaACU1 gene, and the resulting protein not only provided cells with the necessary potassium but also improved their tolerance to toxic lithium. In contrast to its known homologues, CaAcu1 did not seem to transport sodium.
Keywords: membránové transportní proteiny; potassium uptake; draslík; Genetic Complementation Test; proteiny přenášející kationty; Cation Transport Proteins; Potassium; Saccharomyces cerevisiae - proteiny; Recombinant Proteins; Membrane Transport Proteins; Trk1 transporter; Culture Media; kultivační média; Saccharomyces cerevisiae Proteins; rekombinantní proteiny; cation homeostasis; Hydrogen-Ion Concentration; Saccharomyces cerevisiae; Hak1 transporter; Candida albicans; koncentrace vodíkových iontů; Acu1 ATPase; testy genetické komplementace; Candida